Analisis Kebutuhan Strategi Pembelajaran Biologi Berbasis Kearifan Lokal Ekosistem Pesisir - Nur Lina Safitri; Nuril Hidayati; Trio Ageng Prayitno (Jurnal Biologi dan Pembelajarannya (JB&P), 2026)
Biology learning in secondary schools often lacks contextual integration with local ecosystems, particularly in coastal areas. This study aimed to analyze the needs for biology learning strategies based on coastal local wisdom in Pasuruan from the perspective of SMA/MA students. A descriptive quantitative design with a gap analysis approach was employed involving 60 students selected through purposive sampling from SMA/MA schools in coastal Pasuruan. Data were collected using a validated gap analysis questionnaire of 35 items across six dimensions: teaching methods (D1), content contextualization (D2), learning resources (D3), outdoor learning (D4), local wisdom integration (D5), and assessment practices (D6). Findings revealed significant gaps across all dimensions between current conditions (overall mean = 2.33) and desired conditions (overall mean = 4.51), yielding an overall gap score of 2.18. The highest gap was found in D5-local wisdom integration (gap = 2.59), followed by D4-outdoor learning (gap = 2.38), and D2-content contextualization (gap = 2.32). The D1-teaching methods dimension recorded the lowest gap (gap = 1.49). These findings demonstrate a critical need for developing contextually grounded biology learning strategies that systematically embed coastal ecosystem knowledge and local wisdom of the Pasuruan community into secondary school biology instruction